(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
The oil and gas industries remain an essential drive for the world economy. Petroleum geophysical exploration (PGE) significantly impacts the oil industry but is still trapped by fieldwork accidents. This study conducts an analysis of PGE fieldwork accidents, and some potential relationships between the causation and consequence have been suggested. These analysis results illustrate that the accident type that is most likely to occur varies with the conditions of the PGE fieldwork site, which requires a flexible forecasting strategy that suits the actual situation of each fieldwork. From the result, it is suggested that not all the factors impact the specific type of accident. Taking precautions against all types of accidents with the same strategy may not perform well. Allocating too many resources to manage the irrelevant factors is a futility for PGE companies in controlling the fieldwork risk.